Exosome Mediated Cytosolic Cisplatin Delivery Through Clathrin-Independent Endocytosis and Enhanced Anti-cancer Effect via Avoiding Endosome Trapping in Cisplatin-Resistant Ovarian Cancer - Zhou, Guannan; Gu, Yuanyuan; Zhu, Zhongyi; Zhang, Hongdao; Liu, Wei; Xu, Beiying; Zhou, Fangyue; Zhang, Menglei; Hua, Keqin; Wu, Ligang; Ding, Jingxin (Frontiers in Medicine, 2022)
Background: Ovarian carcinoma is one of the most common gynecologic malignancies, cisplatin resistance has become a key obstacle to the successful treatment of ovarian cancer because ovarian carcinomas are liable to drug resistance. To find an effective drug carrier is an urgent need. Methods: Exosomes and loading-cisplatin exosomes are isolated using differential centrifugation and characterized by transmission, electron, nanoparticle tracking analysis. The anti-cancer effect of cisplatin was detected under the circumstance of delivered by exosomes or without exosomes in vitro and in vivo. Using proteome analysis and bioinformatics analysis, we further discovered the pathways in exosomes delivery process. We employed a con-focal immunofluorescence analysis, to evaluate the effects of milk-exosomes deliver the cisplatin via avoiding endosomal trapping. Results: Exosomes and exosome-cisplatin were characterized including size, typical markers including CD63, Alix and Tsg101. The anti-cancer effect of cisplatin was enhanced when delivered by exosome in vitro and in vivo. Mechanistic studies shown that exosomes deliver cisplatin mostly via clathrin-independent endocytosis pathway. Exosomes deliver cisplatin into cisplatin-resistant cancer cells clathrin-independent endocytosis and enhance the anti-cancer effect through avoiding endosome trapping. Conclusion: Cisplatin could be delivered by exosome through clathrin-independent endocytosis, and could evade the endosome trapping, diffused in the cytosol evenly. Our study clarifies the mechanism of exosomes mediated drug delivery against resistant cancer, indicates that exosomes can be a potential nano-carrier for cisplatin against cisplatin resistant ovarian cancer, which validates and enriches the theory of intracellular exosome trafficking. Keywords: exosome;endocytosis; cisplatin-resistant; endosome trapping; exosome trafficking.